CompuCache: Remote Computable Caching using Spot VMs - Zhang, Qizhen; Bernstein, Phil; Berger, Daniel S.; Chandramouli, Badrish; Loo, Boon Thao; Liu, Vincent (Conference on Innovative Data Systems Research (CIDR 2022), 2022)
Data management systems are hungry for main memory, and cloud data centers are awash in it. But that memory is not always easily accessible and often too expensive. To bridge this gap, we propose a new cloud service, CompuCache, that allows data-intensive systems to opportunistically offload their in-memory data, and computation over that data, to inexpensive cloud resources. For reduced cost, each cache is hosted by spot virtual machine (VM) instances when possible or provisioned VMs when not. CompuCache provides a byte-array abstraction and stored procedures so users can easily allocate inexpensive caches and specify their behavior. It distributes each stored procedure execution across the instances. In this paper, we discuss challenges in designing the interface, execution strategy, and fault tolerance mechanisms for CompuCache. We propose initial solutions for them, describe types of applications that can benefit from CompuCache, and report on the performance of an initial prototype. It executes 126 million stored procedure invocations per second on one VM with 16 threads